The Drosophilidae (Diptera) of Estonia - Escher, Stefan; Ekenstedt, Johan; Elberg, Kaupo; Saura, Anssi (Entomologica Fennica, 2006)
Until recently, no published records on drosophilids from the Baltic countries existed, except for an unpublished species list for Estonia. We made two collecting trips through the three Baltic countries in the summer of 2000. The first trip was made in early summer to get spring species and the second in late August to get the fungivorous species. We used baiting methods for collecting Drosophila, while the earlier results were obtained e.g. using net sweeping. In general, the drosophilid fauna of Estonia resembles the well-known fauna of the Nordic countries. The single most interesting result was that Chymomyza amoena, a recent American invader of central Europe, was found. Another interesting finding was the relative rarity of D. subobscura and the virtual absence of D. virilis group species.